2012
DOI: 10.1371/journal.pone.0051884
|View full text |Cite
|
Sign up to set email alerts
|

Development Temperature Has Persistent Effects on Muscle Growth Responses in Gilthead Sea Bream

Abstract: Initially we characterised growth responses to altered nutritional input at the transcriptional and tissue levels in the fast skeletal muscle of juvenile gilthead sea bream. Fish reared at 21–22°C (range) were fed a commercial diet at 3% body mass d−1 (non-satiation feeding, NSF) for 4 weeks, fasted for 4d (F) and then fed to satiation (SF) for 21d. 13 out of 34 genes investigated showed consistent patterns of regulation between nutritional states. Fasting was associated with a 20-fold increase in MAFbx, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…These results were in agreement with the study in Atlantic halibut, where it was also observed that after 7 days of re-feeding, fish that were fasted for 60 days had calpain1 transcript levels significantly decreased, but no differences were observed in calpain2 expression, whereas a significant increase in calpain3 was found [22]. In addition, in a recent study in gilthead sea bream fasted for 4 days, calpain3 expression also increased 5–6 fold 24 h after re-feeding and was maintained until 6 days later [49].…”
Section: Discussionmentioning
confidence: 92%
“…These results were in agreement with the study in Atlantic halibut, where it was also observed that after 7 days of re-feeding, fish that were fasted for 60 days had calpain1 transcript levels significantly decreased, but no differences were observed in calpain2 expression, whereas a significant increase in calpain3 was found [22]. In addition, in a recent study in gilthead sea bream fasted for 4 days, calpain3 expression also increased 5–6 fold 24 h after re-feeding and was maintained until 6 days later [49].…”
Section: Discussionmentioning
confidence: 92%
“…The influence of different temperature ranges during embryonic development on posthatching growth rate in other fish species has also been reported (Macqueen et al, 2008). The effect of different temperature (low temperature: 18°C and high temperature: 22°C) during embryogenesis on muscle growth rate and body mass in gilthead sea bream showed that early temperature treatment has an influence on the expression patterns of a subset of muscle developmental genes (Hsp90a, UNC45, MyoD and IGF1) and their expression is modified by different temperature regimes (Serrana et al, 2012). Interestingly, a positive effect of elevated water temperature on growth rate was observed during post-embryonic development when the animals were reared at three different temperatures: 24°C, 28.5°C and 33°C.…”
Section: Morphometric Traitsmentioning
confidence: 89%
“…Larvae subjected to the highest rearing temperature (22°C) reached the complete yolk‐sac absorption stage in 20% less time than larvae subjected to the lowest temperature (16°C). Likewise, an increase in the rearing temperature caused an increase in the developmental rate in several marine species such as cod Gadus morhua (Pepin et al ., ), Senegalese sole (Campos et al ., ,b) and gilthead sea bream (Garcia de la Serrana et al ., ), and also in freshwater species such as brown trout Salmo trutta (Réalis‐Doyelle et al ., ), Atlantic salmon (Ojanguren et al ., ) and in several other species of sturgeon (Hardy & Litvak, ).…”
Section: Discussionmentioning
confidence: 99%